Quantifying the Resilience of the U.S. Domestic Aviation Network During the COVID-19 Pandemic - Bauranov, Aleksandar; Parks, Steven; Jiang, Xuan; Rakas, Jasenka; González, Marta C. (Frontiers in Built Environment, 2021)
This paper analyzes the impacts of COVID-19 on the U.S. air transportation network between March and August 2020. Despite dramatic reductions in flight and passenger volumes, the network remained robust and resilient against perturbation. While 24% percent of airports closed, the reduction in network efficiency was only 5.1%, which meant airlines continued to serve most destinations. A deeper analysis of airport closures reveals that 1) small peripheral airports were the most likely to be closed; 2) the Coronavirus Aid, Relief, and Economic Security (CARES) Act was a statistically important predictor of closure; 3) socio-economic and epidemiological factors characterizing the airport’s region such as income, income inequality, political leaning, and the number of observed COVID cases were not predictive of airport closure. Finally, we show that high network robustness has a downside; although emissions by the U.S. air traffic in 2020 fell by 37.4% compared to 2019, mostly due to the drop in the number of flights, emissions per passenger doubled in the period April-August 2020, and increased eightfold in the week of April 5-11, which points to inefficient use of resources.